A comparative parasitological, histopathological, and proteomic analysis of Schistosoma mansoni infected mice treated with ivermectin and praziquantel - El-Wakil, Eman Sayed; Tolba, Mona Mohamed; El-Sayad, Mona Hasan; Khairy Hassen, Maha; Al-Rashidi, Hayat S.; Almayouf, Mina A.; Al-Megrin, Wafa Abdullah I.; Alzaylaee, Hind; Moneer, Esraa Abdelhamid (Frontiers in Veterinary Science, 2025)
This study was designed to compare the effectiveness of ivermectin (IVM) with praziquantel (PZQ) in treating Schistosoma mansoni-infected mice through biological and proteomic analysis. Detecting protein structure changes in the worms after treatment could help pursue drug efficacy in schistosomiasis. Sixty Swiss albino mice were infected with S. mansoni cercariae and were divided into three major groups (Infected untreated control, praziquantel-treated, and ivermectin-treated). The evaluation of treatment was performed by parasitological, histopathological analysis, scanning electron microscopy (SEM), and proteomic analysis of the worms through lysis and protein extraction, SDS-PAGE, Mass Spectrometry, and data analysis. The treated groups significantly reduced mean worm load and ova count with smaller granulomas compared to the infected control group. In adult worms treated with PZQ and IVM, severe tegumental destruction, peeling, erosion, ulceration, and suckers damage were detected by SEM. The proteomic study identified 19 protein bands, 12 commonly shared proteins between all studied groups, and seven differential protein bands. Molecular and biological function administered from the NCBInr database revealed the presence of glycolytic proteins, structural proteins, and cytosol stress response. Although praziquantel outperformed ivermectin, the anti-schistosomal properties of ivermectin are encouraging, evidenced by changes in the protein structure of the worms detected after ivermectin treatment. This may open the way to use ivermectin in combination with other anti-schistosomal medicines to avoid any potential resistance from monotherapy. Besides, it highlights the role of proteomic analysis in differential protein identification that could help efficiently treat schistosomiasis.